Borders, Citizenship, and Global Inequality: What Barriers, Pushbacks, and Passport Controls Reveal About Our Understanding of the Equality of Humankind - Towfigh, Emanuel V.; Weyl, Niklas T. (German law journal, 2025)
Borders are ubiquitous. As invisible lines, they contribute to a functioning world order and guarantee security for the people. In the form of walls and fences, they divide society and establish strongholds of prosperity that are not accessible to everyone. A similar effect can be observed in connection with the concept of citizenship, which binds people fatefully to a particular territory and thus significantly determines an individual’s life chances. This article shows how borders and their protection as well as the concept of citizenship challenge fundamental ideas of justice and traces discourses that seek to evolve the current border and citizenship regimes into a more universal and just form of human coexistence.